United States Jewry, 1776-1985 Volume 1 - Rader Marcus, Jacob (Wayne State University Press, 2018)
In United States Jewry, 1776-1985, the dean of American Jewish historians, Jacob Rader Marcus, unfolds the history of Jewish immigration, segregation, and integration; of Jewry's cultural exclusiveness and assimilation; of its internal division and indivisible unity; and of its role in the making of America. Characterized by Marcus's impeccable scholarship, meticulous documentation, and readable style, this landmark four-volume set completes the history Marcus began in The Colonial American Jew, 1492-1776. Volume I focuses on the American revolution and the early national period, from 1776 to 1840. Marcus examines the role played by Jews in the revolution and discusses important historical and social themes such as politics, commerce, religion, Jewish and American culture, anti-Jewish prejudices, and the phenomenon of assimilation.